Learning Mathematics Using a Collaborative RME Approach in the Indoor and Outdoor Classrooms to Improve Students' Mathematical Connection Ability - Didik Sugeng Pambudi; Sunardi Sunardi; Titik Sugiarti (Jurnal Pendidikan Matematika, 2022)
Teaching approach applied by mathematics teacher can affect students' mathematical connection ability (MCA). The fact shows that there are still many teachers using conventional learning, causing passive students and low MCA among students. The purpose of this study was to describe the effectiveness of applying a collaborative realistic mathematics education (RME) approach using the classroom and the outdoor environment to improve students' MCA on the topic of similar triangles. This quasi-experimental research with a qualitative descriptive approach took the subject of ninth-grade students at a public junior high school in Jember, Indonesia. Data were collected using observation sheets, questionnaires, tests, and interviews. The data were analyzed using the effectiveness test (N-gain score). The results showed that the application of collaborative RME using the indoor and outdoor classrooms made students more active in physical, social, and mental activities. This learning is effective in improving students' MCA. The average score of 57.47 in the pre-test increased to 93.88 in the post-test, and the N-gain score was 0.86. Mathematics teachers are advised to apply this learning approach, not only on the topic of similarity triangles, but also on other suitable topics.